Deep Immunophenotyping of Circulating T and B Cells in Relapsing Adult-Onset Still’s Disease - Myachikova, Valentina; Kudryavtsev, Igor; Rubinstein, Artem; Aquino, Arthur; Isakov, Dmitry; Golovkin, Alexey; Maslyanskiy, Alexey (Current Issues in Molecular Biology, 2024)
Adult-onset Still’s disease (AOSD) is a complex systemic inflammatory disorder, categorized as an ‘IL-1 driven’ inflammasomapathy. Despite this, the interaction between T and B cells remains poorly understood. We conducted a study, enrolling 7 patients with relapsing AOSD and 15 healthy control subjects, utilizing deep flow cytometry analysis to examine peripheral blood T- and B-cell subsets. T-cell and B-cell subsets were significantly altered in patients with AOSD. Within CD4+ T cells, Th2 cells were decreased. Additionally, Th17 cell and follicular Th cell subsets were altered within CD45RA–CD62L+ and CD45RA–CD62L– Th cells in patients with AOSD compared to healthy controls. We identified changes in CD8+ T cell maturation and ‘polarization’ in AOSD patients, with an elevated presence of the TEMRA CD8+ T cell subset. Furthermore, the percentage of Tc1 cells was decreased, while the frequency of CCR6–CXCR3– Tc2 cells was elevated. Finally, we determined that the frequency of CD5+CD27– B cells was dramatically decreased in patients with AOSD compared to healthy controls. Further investigations on a large group of patients with AOSD are required to evaluate these adaptive immunity cells in the disease pathogenesis.